Dampak Malas Belajar pada Mahasiswa Prodi PPKN di Kampus Universitas Bhinneka PGRI Tulungagung - Pradana, Fannes Angga; Hasib, Mohammad (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
Laziness to learn in students has an impact on decreasing academic achievement, inhibiting their potential, and decreasing the quality of graduates. Internal factors such as lack of discipline, as well as external factors such as uninteresting learning methods and unsupportive environment, contribute to this condition. Therefore, it is necessary to study the impact to find the right solution. The purpose of this study was to identify the causes of PPKN study program students on the campus of Bhinneka PGRI Tulungagung University being lazy in learning and to analyze the impact of lazy learning on PPKN study program students on the campus of Bhinneka PGRI Tulungagung University. The method used in this research is qualitative ethnomethodology, data collection through observation, interviews, and documentation. Lazy learning behavior in PPKN Study Program students at Bhinneka PGRI Tulungagung University is caused by various factors, including decreased enthusiasm and motivation, poor time management, a less conducive learning environment, and the influence of the social environment and peers. The four factors are interrelated and have a significant impact on the process and results of student learning. The impact includes a decrease in academic performance, lack of participation in lecture activities, psychological pressure, and the desire to leave or even drop out. Thus, lazy learning is not only an individual problem, but also reflects the need for students to learn.